The Role of Customer Intention Regarding Environmentally Sustainable Islamic Banking in Indonesia: Examining the Structural Model - Sodik, Fajar; Mahfuzh, Muhammad Ady; Olivia, Diana (Universitas Islam Internasional Indonesia, 2023)
Environmental degradation is a global concern for businesses, requiring consistent effort to maintain sustainable environmental practices. Environmental sustainability is a crucial issue of concern to everyone, an increasing proportion of people are paying attention to various environmental issues in all parts of their lives, including in the context of Islamic banking. This research aims to develop and test a contextual framework for studying customer intentions in adopting sustainability Islamic banking activities and services. The study uses the Theory of Planned Behavior (TPB) model, adding new constructs to the main variables, such as trust, environmental consciousness, and perceived environmental outcomes. The survey collected data from 198 customers of Islamic banks in Indonesia, with the PLS-SEM modeling technique used to test the research model. The results show that perceived behavioral control is a significant influence on behavioral intentions, while attitude and subjective norms have no significant effect on behavioural intentions. Environmental consciousness significantly affects perceived environmental outcomes, which, in turn, significantly affect trust as well as behavioural intentions. Other statistical results find that environmental consciousness can affect behavioral intentions when mediated by perceived environmental outcomes. Overall, this study has theoretical and managerial implications and offers directions for future research on environmentally sustainable Islamic banking.